Characteristics and formation factors of strategies for social adaptation to COVID-19 among the population of the Republic of Belarus - Shkurova, Alena V.; Navitsky, Yauhen N.; Kudrevich, Maxim A. (Journal of the Belarusian State University. Sociology, 2022)
The article presents the results of public opinion study on COVID-19 in the Republic of Belarus. The strategies of social adaptation implemented by the population are presented and described in accordance with the developed model of the typology of methods of social adaptation. The key parameters for constructing a typology are the level of anxiety, self-identification with the type of reaction, the frequency of tracking information about COVID-19; a variety of preventive measures performed. In addition, based on the comparison of the described behaviours with other indicators, one can judge the specifics of the social portrait of adherents of various strategies, the specifics of choosing sources of information about COVID-19 and the frequency of their use, the dynamics of attitudes towards the medical field, including vaccination. The system of social control and the adoption of preventive measures in educational and professional organisations are essential for the formation of strategies for social adaptation.
Keywords: spread of COVID-19; sociological research; social adaptation; social adaptation strategies; social norm; interiorisation